Manajemen Pembiayaan Pendidikan Islam di Sekolah - Damanhuri, Faiz Madani; Sa'diyah, Maemunah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The purpose of this study is to find out the principles of Islamic education financing management management in schools. This study uses library research, so the method used in the research is literature study. Where the researcher is directly confronted with the data or text presented, not with field data or through eyewitnesses in the form of events, the researcher is only directly confronted with sources that are already in the library or ready-to-use data, as well as secondary data used. The results of this study show that financing in Islamic educational institutions must have financing management principles in managing Islamic educational institutions, namely the principles must be based on honesty and transparency that maintain integrity in all financial transactions, make accurate and open financial records. Therefore, it is concluded that by applying these principles, Islamic education financing management can run well, effectively, and in accordance with religious teachings, thereby supporting the achievement of quality and equitable education goals.